Copolymerization of norbornene and butyl methacrylate at elevated temperatures by a single centre nickel catalyst bearing bulky bis(α-diimine) ligand with strong electron-withdrawing groups. Issue 15 (30th March 2017) - He, Xiaohui; Deng, Yingjiao; Jiang, Xiong; Wang, Zijie; Yang, Yingping; Han, Zhilong; Chen, Defu
Abstract : Bis(α-diimine) single nickel(ii ) catalyst with strong electron-withdrawing group was applied to catalyze polymerization and copolymerization of norbornene and butyl methacrylate. Abstract : A bulky α-diimine ligand with a three dimensional geometry and strong electron-withdrawing groups (–NO2 ), 9, 10-dihydro-9, 10-ethanoanthracene-11, 12-di( p -PhNO2 )imine(L ), and a corresponding single nickel catalyst (NiL2 Br2 ) were synthesized, and the molecular structure of theNiL2 Br2 catalyst was confirmed by X-ray crystallography. After being activated with B(C6 F5 )3, theNiL2 Br2 catalyst exhibited high activity towards homopolymerization and copolymerization of norbornene(NB) and butyl methacrylate (BMA). The obtained poly(NB- co -BMA)s were confirmed to be vinyl-addition copolymers and noncrystalline. The BMA monomer content in the copolymers could be controlled up to 6.0%–78.7% by varying the BMA monomer feed ratios from 10% to 90%. The obtained poly(NB- co -BMA)s exhibited high thermal stability ( T d > 390 °C), high-molecular-weight and narrow molecular weight distribution (PDI ≤ 1.4) and could be processed into films with good transparency and mechanical properties.